Chemical compounds in essential oil of nutmeg leaves (Myristica fragrans) from Batang Indonesia. Issue 1 (July 2021) - Kusumaningrum, H P; Zainuri, M; Endrawati, H; Loka, B D; Widiasa, I N; Sulistyowati, E
Abstract: Nutmeg oil has an important function as natural tropical biomedicine activity which commonly found in Batang region. This essential oil is one of the dominant traditional export product from Batang instead of patchouli oil, Clove oil, and lemongrass oil. The objective of the research was to analyze chemical compound of essential oil of nutmeg leaves from Batang region produced by traditional destillation. Research methods was conducted by GCMS method. The biomedical activity against some tropical diseases was analysed in-silico. The results showed that essential oil from nutmeg leaves showed potential antimicroabial activities in silico againts several tropical diseases in skin. The GCMS result showed 2-.BETA.-PINENE and .gamma.-Terpinene as the major compound with values 34, 46% and 30, 28%.